O impacto da desaposentação nas contas da Previdência - Londucci, Silmara (2015)
The unretirement figure was brought up due to the mandatory contribution of nonoperative concurrently with the termination of the gratuity, which exposed the possibility - only through legal process, - to request the resignation to retirement and apply for a new retirement accounting the received value with the contributions of the period contributed after the retirement. The main hindrances that either pension funds or social security face concern to demographic adversities, such as the aging of the population that associated with a decline in mortality and fertility, may contribute greatly in Social Security collection of subsistence in the long term. The aim of this study is to evaluate the impact of unretirement in RGPS ; boiling down to the fact that there isn t much impact at the government expenses, after all, unlike many previous studies. And that this impact, if any, can be supplanted by strict compliance the Lei Maior in the way it was planned by Constituents by the efficient management - since the principle of public service efficiency is a corollary of public administration. This subject has a great deal of controversy, hence, the goal to explore it. For once there is the debate about the economic impact on the social security accounts, and second, because Brazil, if not the only, is one of the only few countries that charges contribution inactive, a fact that needs reconsideration revised in view of the volume of revenue collected by the Social Security annually. The collection of social security contribution by retirees also generates large public spendings in the judiciary, with thousands of lawsuits filed and the whole structure of the judicial machinery to meet the citizens who are in the same situation